Annexin A2 and lamin B join membrane recycling compartments for the assembly of biomolecular condensates operating in mitotic partitioning - Grindheim, Ann Kari; Dale, Hege; Novák, Josef; Patil, Sudarshan Shantinath; Vedeler, Anni; Saraste, Jaakko (Frontiers in Cell and Developmental Biology, 2026)
Localization of the actin-, lipid- and mRNA-binding protein Annexin A2 (AnxA2) in dividing cells revealed its presence in large spherical structures which are confined to the cell periphery and frequently co-align with astral microtubules. These structures appear during prometaphase and disappear at telophase, coinciding with the mitotic breakdown and subsequent reformation of the nuclear lamina and envelope. Their size increases as cells progress to anaphase, while their number decreases, suggesting that they are capable of fusion. Treatment of cells with the aliphatic alcohol propylene glycol led to rapid and reversible disassembly of the structures, providing further evidence that they correspond to biomolecular condensates. Notably, the condensates enclose compartments involved in biosynthetic or endocytic membrane recycling – defined by Rab1, Rab11, or endocytosed transferrin–but lack other membrane organelles, indicating that they may serve as mitotic reservoirs for selected endomembranes. Additionally, the condensates incorporate lamin B, which connects with the pericentrosomal membrane recycling compartments during prometaphase, when the nuclear lamina disassembles in conjunction with centrosome separation. These findings show similarities between the peripheral mitotic condensates and the membranous lamin B spindle matrix which has been proposed to act in spindle organization and organelle inheritance. The separating daughter cells at late anaphase contain equal numbers of the condensates, in accordance with their potential role in mitotic partitioning of endomembranes and other cytoplasmic components.